The self-regulation of teleological thinking in natural selection learning - Gonzalez Galli, Leonardo Martin (2020)
Background: Teleology is one of the critical aspects of students' intuitive concepts about living beings and, specifically, their evolution. This cognitive bias imposes a substantial restriction on the process of learning such content. In this work, we rely on epistemological, psychological and pedagogical analyses to substantiate an educational proposal centered on the concepts of epistemological obstacles and metacognitive vigilance. Results: Based on Michael Ruse's epistemological analysis, according to which teleology in biology persists because the scientific explanation of adaptation necessarily involves appeal to the metaphor of design, and on research in cognitive psychology, especially in relation to metacognition and self-regulated learning, we argue that the primary educational aim must be to encourage students to develop metacognitive skills to regulate the use of teleological reasoning. We develop our instructional proposal based on the didactic concepts of epistemological obstacles and metacognitive vigilance (consistent with epistemological and psychological analyses). Conclusion: We briefly discuss the instructional implications of our analysis and some possible relationships between our proposal and other lines of research in psychology and science education.